Research progress on value-added utilization of carbon dioxide through bio-electro-catalysis - Jiale XIE; Tianyu ZHANG; Zhangdi PENG; Richen LIN; Rui XIAO (Meitan xuebao, 2024)
China is the world’s largest CO2 emitter and coal consumer, and its coal dominated energy structure is difficult to be changed in the short term. In the context of carbon peaking and carbon neutrality, the capture and storage or conversion of carbon dioxide into renewable fuels and chemicals can reduce dependence on fossil fuels and at the same time reduce CO2 emissions, providing key technical support for the green transition of coal-fired power plants and energy chemicals. Electrocatalysis and microbial conversion are important ways to produce renewable fuels and chemicals from carbon dioxide. The reaction rate of electrocatalytic reduction of CO2 is high, but the products are mostly limited to C1 and C2 products. Microbial CO2 fixation has the advantages of high selectivity and variety of products. However, the low electron transfer and energy supply lead to a long reaction period in the microbial CO2 fixation. Integration of electrocatalysis and microbial conversion can play their advantages to efficiently produce the value-added multi-carbon products. In this paper, firstly, the reaction principles, typical products of electrocatalysis and microbial CO2 fixation under a single technical route were introduced respectively. The catalyst and reactor of electrocatalytic CO2 reduction were discussed, and the microbial species and biological metabolic pathways of microbial fixation of CO2 were summarized. Secondly, two methods of the integration of electrocatalysis and microbial conversion was reviewed, and the system structure, working principle, electrode materials and value-added products were analyzed. Finally, the technology readiness level of different coupling methods was compared, and the future prospects were highlighted from four aspects: the catalysts for electrocatalytic CO2 reduction, the engineered microbial strains, the design and integration of coupling systems and the linkage between academic research and industry.